ANALISIS PENGARUH TRUST DAN BRAND IMAGE TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN DI PT DELTA SATRIA DEWATA BALI - LUH KOMANG CANDRA DEWI; STEVANUS KAKOMORE; I WAYAN TERIMAJAYA (GANEC SWARA, 2023)
market share. An important factor that must be considered by distribution companies is to maintain customer satisfaction and loyalty. The number of competitors in the same business certainly makes entrepreneurs think how to prevent consumers who are familiar with their company's products/brands from moving to other places. The purpose of this study is to analyze the effect of trust and brand image on customer satisfaction and loyalty at PT. Delta Satria Dewata Bali.The location of this research is at PT. Delta Satria Dewata Bali, Jl Imam Bonjol No. 226A. The sampling technique used was non-probability sampling, namely the purposive sampling method with a total sample of 100 respondents. The data collection method used a questionnaire with a likert (5 scale). The data analysis technique used is path analysis.The results showed that the variables of trust and brand image had a positive and significant effect on customer satisfaction at PT. Delta Satria Dewata Bali. Variables Trust and brand image have a positive and significant effect on customer loyalty at PT. Delta Satria Dewata Bali. The variable of customer satisfaction has a positive and significant effect on customer loyalty at PT. Delta Satria Dewata Bali